The Basic Cycles of Vocational Training: Student Satisfaction and Perceived Benefit - María José Martínez-Carmona; Carmen Gil del Pino; José Luis Álvarez-Castillo (MDPI AG, 2022)
This study aims to better understand students who attend Basic Vocational Training Cycles (Basic Professional Training, BTP) by implementing measures that ensure diversity. This quantitative research project approximated students' perception of their passage through previous studies and their satisfaction and goals after finishing the school year. The sample consisted of 352 students from Cordoba (Spain). A questionnaire was used that follows the CIPP model. After exploratory factor analysis was completed with different groups of items and their descriptive analyses, various tests were carried out to consider the hypotheses (Pearson's correlation (r), one-factor analysis of variance, and repeated ANOVA measures). The results indicate that the educational interest of the students is academic and professional. Likewise, there is no relationship detected between socio-professional goals and average academic levels and attributions with respect to repetitions of previous courses, although these goals vary depending on students' satisfaction with the vocational cycles. We conclude that the course of the FPB influences decisions regarding academic-professional projects.